Alfabetización en Chimborazo, a través de las Escuelas Radiofónicas Populares de Ecuador, período 1962-1986 y su relación con la Pedagogía de la Liberación de Paulo Freire - Cayambe Chimbo, Jessica Maribel (2022)
The research is based on the literacy that was developed in the 60's in the province of Chimborazo directed especially to adults that later would include young people, a notion that was implemented by Leonidas Proaño Villalba, after becoming Bishop of Riobamba and feeling the reality in which the indigenous people live and his love for the poor that was closely linked to the Liberation Theology, influenced by the thought of Paulo Freire who proposed a liberating education certainly for those made invisible within the Latin American history. This research has a qualitative approach therefore the instrument applied for the collection of information is an interview guide applied to experts and people close to the literacy process. The theoretical foundation supports the research work, which demonstrates the needs and conditions in which the indigenous people of Chimborazo lived, the change that literacy represents for these sectors from their reality; this was the basis of the pedagogy of liberation, to form the criticality and allow the oppressed themselves to break the ties they brought from the colony. It was necessary to mention the work of Escuelas Radiofónicas Populares del Ecuador (ERPE) which is the axis of social transformations and an educational medium that could reach the most remote sectors and its novel arrival marks a before and after in the indigenous bases that is reflected in texts and research that help to support the new lines of research.